Three‐Dimensional Carbon‐Coated SnO2/Reduced Graphene Oxide Foam as a Binder‐Free Anode for High‐Performance Lithium‐Ion Batteries. Issue 7 (2nd May 2016) - Tao, Huachao; Zhu, Shouchao; Xiong, Lingyun; Yang, Xuelin; Zhang, Lulu
Abstract: A three‐dimensional carbon‐coated SnO2 /reduced graphene oxide (SnO2 /RGO/C) foam has been prepared by using glucose as the carbon source and cross‐linking agent through a one‐step hydrothermal process followed by freeze drying. The foam, as a free‐standing anode for lithium‐ion batteries, exhibits a large capacity and excellent cycling stability (717 mAh g −1 after 130 cycles at 100 mA g −1 ). The outstanding electrochemical performance could be related to the synergistic effect between the nano‐sized high‐capacity SnO2, the excellent electronic conductivity and large specific surface area of RGO, and the carbon coating layer, which could enhance the bonding strength of SnO2 nanoparticles and RGO nanosheets, keep the structural integrity, and increase the electronic conductivity. The strong interaction between SnO2 and RGO, the high electronic conductivity, and the porous structure of the composite result in high electrochemical activity and stable cycling performance as a binder‐free anode for lithium‐ion batteries. Abstract : Integral part : Three‐dimensional carbon‐coated SnO2 /reduced graphene oxide (RGO) foam is prepared through a one‐pot hydrothermal method followed by freeze drying. The foam, as a free‐standing anode for lithium‐ion batteries, exhibits a large capacity and excellent cycling stability. The carbon layer enhances the bonding strength of SnO2 nanoparticles and RGO nanosheets and maintains the structural integrity.